Mitraclip therapy in patients with functional mitral regurgitation and missing leaflet coaptation: is it still an exclusion criterion?. (22nd April 2016) - Adamo, Marianna; Chiari, Ermanna; Curello, Salvatore; Maiandi, Cristian; Chizzola, Giuliano; Fiorina, Claudia; Frontini, Mario; Cuminetti, Giovanni; Pezzotti, Elena; Rovetta, Riccardo; Lombardi, Carlo Mario; Manzato, Aldo; et al.
Abstract: Aims: The aim of this study was to investigate the feasibility, safety, and efficacy of Mitraclip therapy in patients with functional mitral regurgitation (MR) and missing leaflet coaptation (MLC). Methods and results: Out of 62 consecutive patients with functional MR undergoing Mitraclip implantation, 22 had MLC defined as the presence of a 'gap' between two mitral leaflets or insufficient coaptation length (<2 mm), according to the EVEREST II criterion. Compared with the control group, the MLC population had a significantly higher effective regurgitant orifice area (0.67 ± 0.31 vs. 0.41 ± 0.13 cm 2 ; P = 0.019) and sphericity index (0.80 ± 0.11 vs. 0.71 ± 0.10; P = 0.003). MLC patients were treated with pharmacological/mechanical support in order to improve leaflet coaptation and to prepare the mitral valve apparatus for grasping. Implantation of >1 clip and device time were comparable in patients with and without MLC (61.9% vs. 47.5%; P = 0.284 and 101 ± 39 vs. 108 ± 69 min; P = 0.646, respectively). No significant differences were observed between the two cohorts in technical success (95.5% vs. 97.5%, P = 0.667), 30‐day device success (85.7% vs. 78.9%; P = 0.525), procedural success (81.8% vs. 75%; P = 0.842), and 1‐year patient success (52.9% vs. 44.1%; P = 0.261), defined according to the MVARC (Mitral Valve Academic Research Consortium) criteria. The long‐term composite endpoint of cardiovascular death and heart failure hospitalization was similar in the two groups (49.9% vs. 44.4%; P = 0.348). A significant improvement of MR and NYHA functional class and a lack of reverse remodelling were observed up to 2 years in both arms. Conclusion: The Mitraclip procedure could be extended to patients with functional MR who do not fulfil the coaptation length EVEREST II criterion and who would otherwise be excluded from this treatment.